Arbeitszufriedenheit und Persönlichkeit: "Wer schaffen will, muss fröhlich sein!" - Simon Fietze (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
– The research on job satisfaction has a long history and is one of the most intensively studied subjects - not only in the field of industrial and organizational psychology. The various studies can roughly be classified into situational, dispositional, and hybrid approaches, depending on whether working conditions, personality traits or their interaction are emphasized as determinants. So far, only few studies consider all of these determinants in a common model. In addition, many studies both in the consideration of personality variables as well as the influence of factors to explain job satisfaction, do not offer a theoretical framework. This paper investigates the influence of personality characteristics and working conditions as well as the interaction of these two groups of variables on job satisfaction by means of the German Socio-Economic Panel (SOEP) study. For this purpose, the Five-Factor Model (FFM) of personality (P. T. Costa und R. R. McCrae 1985; L. R. Goldberg 1981) and the Effort-Reward Imbalance Model (J. Siegrist et al. 1986) will be used as a theoretical and conceptual framework. OLS regressions show that both personality and (subjective) working conditions are relevant predictors of job satisfaction. None of the moderator variables of personality and working conditions increase the explained variance of the overall model. Working conditions (effort-reward imbalance and autonomy) have the highest explanatory power. Four of the five personality traits show highly significant effects. These findings suggest both a situational and a dispositional approach. Working conditions(especially a low effort-reward imbalance and high autonomy) and personality (especially emotional stability) play a crucial role in achieving higher job satisfaction.
Keywords: J28; M12; 330; Job satisfaction; personality; Five-Factor Model; Big Five; Effort-Reward Imbalance; Arbeitszufriedenheit; Arbeitsbedingungen; Persönlichkeitspsychologie; Schätzung; Deutschland